1990
DOI: 10.1007/bf01624525
|View full text |Cite
|
Sign up to set email alerts
|

Left-right asymmetry of the temporal and parietal regions in children: based on the medullary pattern of cerebral white matter

Abstract: Lateralization of the posterior temporal lobe and inferior parietal lobule in childhood was studied on CT of 276 cases and compared with those in adulthood of 371 cases. CT images were analyzed based on the morphological features of medullary branches of the cerebral white matter. In children below 5 years of age, the left planum temporale was already more posteriorly located than the right in 56%, while the right was more so in 21%. The asymmetry of the middle temporal gyrus was similar to those of the planum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This study replicates previous studies in which the IPL showed leftward asymmetry (Eidelberg and Galaburda, 1984;Iwasaki et al, 1986Iwasaki et al, , 1990Raz et al, 1997). However, this study is the first to identify sex differences with respect to left, but not right, IPL gray matter volume, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study replicates previous studies in which the IPL showed leftward asymmetry (Eidelberg and Galaburda, 1984;Iwasaki et al, 1986Iwasaki et al, , 1990Raz et al, 1997). However, this study is the first to identify sex differences with respect to left, but not right, IPL gray matter volume, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Because our study did not separate the angular and the supramarginal gyri, we are unable to compare our volumes with those of the Eidelberg and Galaburda study. Iwasaki et al found more intricate and extensive folding of the left IPL in 500 adults by examining cerebral white matter medullary branching patterns on CT (Iwasaki et al, 1986). In a later study with 276 children, the same group (Iwasaki et al, 1990) demonstrated that childhood patterns did not differ significantly from those found in adults.…”
Section: Tablementioning
confidence: 95%
“…As mentioned, the structures, size, and other functions of two hemispheres in many cortical regions are asymmetrical. Iwasaki et al 46 found left-to-right differences in cerebral structures of the parietal and temporal region by an anatomic analysis of the medullary branches after the a computed tomographic examination. Mottaghy et al 47 found that interference by TMS on the verbal working memory occurs earlier, after stimulation of the right than of the left hemisphere.…”
Section: Effect On Combined Saccade-vergence Movementsmentioning
confidence: 98%
“…The supratemporal plane has conventionally been analyzed morphologically and radiologically by 2-D plane observation, which is not appropriate for analyzing a plane with a complicated 3-D structure (7)(8)(9)(10)(11)15). In recent years advances have been made in the display of 3-D images by CT (1, 16) and MR imaging (3,12,14).…”
Section: Discussionmentioning
confidence: 99%